DOI: 10.31274/rtd-180813-7611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage and crop rotation on soil nitrate and moisture

Abstract: Alachlor c 2.2 Atrazine c 2.8 Alachlor 2.2 Atrazine 2.8 Alachlor 2.2 Cyanazine c 2.8 Alachlor 2.2 Cyanazine 2.8 Alachlor 2.2 Metribuzin c 0.45 a Active ingredient .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Plots used in this study were located in Readlyn, and Kenyon soil types (table 2). Soil physical properties, including percent sand, silt, and clay, available water, bulk density, and saturated hydraulic conductivity at different depths for each soil type, were measured at the site by Ratliff et al (1983), Weed (1992), and Mirjat (1992). These data are shown in table 1.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…Plots used in this study were located in Readlyn, and Kenyon soil types (table 2). Soil physical properties, including percent sand, silt, and clay, available water, bulk density, and saturated hydraulic conductivity at different depths for each soil type, were measured at the site by Ratliff et al (1983), Weed (1992), and Mirjat (1992). These data are shown in table 1.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…Many studies demonstrated the importance of the application of fertilizer at rates not exceeding the optimal crop demand (Mercado, 1976;Varvel and Peterson, 1990;Weed and Karlen, 1992;Puckett et al, 1999). Puckett et al (1999) cited many studies that estimated a fertilizer application rate that is 24 to 38 percent higher than the crop demand.…”
Section: Alternative 2: Reduction Of Fertilizer Applicationmentioning
confidence: 99%
“…These cores were composited after sectioning them into a set of nine samples representing the following depths: 0 to 0.10, 0.10 to 0.20, 0.20 to 0.30, 0.30 to 0.45, 0.45 to 0.60, 0.60 to 0.90, 0.90 to 1.20, 1.20 to 1.50, and 1.50 to 1.80 m. Composited samples were analyzed for soil water content, NO3-N, and pesticide concentrations. A detailed methodology of collecting soil samples and analyzing them is described by Weed (1992). Simulated NO3-N concentration in the soil profile were compared with the measured NO3-N concentration for 1990 and 1992.…”
Section: No3-n Concentrations In the Soil Prohlementioning
confidence: 99%